The Concept of Integration of Science and Islam in Higher Education Perspective of M. Natsir - Patahuddin, Askar; Hafidhuddin, Didin; Indra, Hasbi; Handrianto, Budi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find the concept in Indonesian universities that integration by science and religion in their regulations. The research employs a qualitative method with a historical-philosophical approach, conducting content analysis on the thoughts of M. Natsir to generate a new concept. The research findings indicate, firstly, that the concept of integrating science and Islam in higher education from M. Natsir's perspective involves the integration of Islamic knowledge and general knowledge without secularizing science and Islam. This integration includes mastering foreign languages, particularly Arabic, instilling moral values through ta’dib, enhancing learning through the presentation of arguments, advising, and adopting a wise approach with efforts in higher education to orient graduates towards becoming strong and sincere preachers.